2013
DOI: 10.1074/jbc.m113.512640
|View full text |Cite
|
Sign up to set email alerts
|

The Cyclin-dependent Kinase Inhibitor p16INK4a Physically Interacts with Transcription Factor Sp1 and Cyclin-dependent Kinase 4 to Transactivate MicroRNA-141 and MicroRNA-146b-5p Spontaneously and in Response to Ultraviolet Light-induced DNA Damage

Abstract: Background: The cyclin-dependent kinase inhibitor p16INK4a is also a modulator of gene expression through an unknown mechanism. Results: p16INK4a -CDK4 forms a heterocomplex with Sp1, which induces the expression and UV-dependent up-regulation of miR-141 and miR-146b-5p. Conclusion: p16INK4a -CDK4 complex has transcriptional activity through interaction with the transcription factor Sp1. Significance: The microRNAs are novel effectors of the p16INK4a -CDK4 complex.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
44
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
2

Relationship

5
4

Authors

Journals

citations
Cited by 35 publications
(46 citation statements)
references
References 50 publications
2
44
0
Order By: Relevance
“…That is to say, SP1 is a direct target gene of miR-374. A recent study has demonstrated that by interacting with p16 INK4a through the fourth ankyrin repeat, SP1 could combine with the promoters of miR-141 and miR-146b-5p and their transcriptional activation [18]. Recently, a study showed that within the Bcl-2 and SP1 mRNA 3'UTRs, miR-429 could combine with putative binding sites to lower their expression; through targeting Bcl-2 and SP1, up-regulation of miR-429 could depress invasion and advance apoptosis in esophageal carcinoma cells, indicating that Bcl-2 and SP1 could be major targets of miR-429 [19].…”
Section: Discussionmentioning
confidence: 99%
“…That is to say, SP1 is a direct target gene of miR-374. A recent study has demonstrated that by interacting with p16 INK4a through the fourth ankyrin repeat, SP1 could combine with the promoters of miR-141 and miR-146b-5p and their transcriptional activation [18]. Recently, a study showed that within the Bcl-2 and SP1 mRNA 3'UTRs, miR-429 could combine with putative binding sites to lower their expression; through targeting Bcl-2 and SP1, up-regulation of miR-429 could depress invasion and advance apoptosis in esophageal carcinoma cells, indicating that Bcl-2 and SP1 could be major targets of miR-429 [19].…”
Section: Discussionmentioning
confidence: 99%
“…The possible mechanisms by which miR-141 downregulated in GC might be that miR-141 was regulated by certain transcriptional factor (Sp1) [23] or decreased by H. pylori infection [11]. MiR-141 could target with oncogene STAT4 and ZEB1 [21] to regulate GC cell functions.…”
Section: Discussionmentioning
confidence: 99%
“…INK4a , hereafter referred to as p16, negatively regulates the expression of AUF1 through activating the turnover of its mRNA (10) and also positively regulates the expression of miR-141 and miR-146b-5p, two important tumor suppressor miRNAs (21). Interestingly, the two miRNAs have been computationally predicted to have binding sites in the 3Ј-UTR of the AUF1 transcript (22) but have not been experimentally validated.…”
mentioning
confidence: 99%